2022
DOI: 10.3389/fphar.2022.965789
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide hexadecyl ester targeted plga nanoparticles for drug-resistant glioblastoma therapy via intranasal administration

Abstract: Introduction: Temozolomide (TMZ) is the first-line drug for glioblastoma (GBM), but it is limited in clinical use due to the drug resistance, poor brain targeting, and side effects. Temozolomide hexadecyl ester (TMZ16e), a TMZ derivative with high lipophilicity, membrane permeability, and high anti-glioma properties, has the potential to reverse drug resistance. In this study, anti-ephrin type-A receptor 3 (EphA3) modified TMZ16e loaded nanoparticles (NPs) were prepared for targeted GBM therapy via intranasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…To confirm the safety of PLGA NPs and SLNs in the brain microenvironment, both particle types have been studied in vitro for compatibility with neurons and other resident brain cells. PLGA NPs did not affect the integrity of human SH-SY5Y neuroblastoma cells, monocytes, and 16 HBE epithelial cells used to model the BBB, rodent PC12 catecholaminergic neurons, brain endothelial cells, primary microglia and primary astrocytes, or murine hippocampal neurons, N2a neuroblastoma cells, and N9 microglia [ 38 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Notably, prolonged PLGA NP exposure did not alter neuronal morphology or affect the viability of primary rat neuronal-glial mixed cultures up to concentrations of 2.5 mg/mL [ 61 ].…”
Section: Nanotechnology For Bbb Crossingmentioning
confidence: 99%
See 2 more Smart Citations
“…To confirm the safety of PLGA NPs and SLNs in the brain microenvironment, both particle types have been studied in vitro for compatibility with neurons and other resident brain cells. PLGA NPs did not affect the integrity of human SH-SY5Y neuroblastoma cells, monocytes, and 16 HBE epithelial cells used to model the BBB, rodent PC12 catecholaminergic neurons, brain endothelial cells, primary microglia and primary astrocytes, or murine hippocampal neurons, N2a neuroblastoma cells, and N9 microglia [ 38 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Notably, prolonged PLGA NP exposure did not alter neuronal morphology or affect the viability of primary rat neuronal-glial mixed cultures up to concentrations of 2.5 mg/mL [ 61 ].…”
Section: Nanotechnology For Bbb Crossingmentioning
confidence: 99%
“…Robust in vitro models of brain cancers exist, which involve culturing tumour cells and testing drug efficacy by measuring cell death. PLGA NPs loaded with a derivative of the anti-cancer drug temozolomide were non-toxic to 16HBE cells but reduced the viability of T98G GBM cells to 20% of control [ 58 ]. Doxorubicin-entrapped SLNs induced cell death when applied to U87MG GBM cells [ 74 ].…”
Section: Nanotechnology For Bbb Crossingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts were made to formulate PGLA-based NPs to effectively deliver drugs to GBM cells, including methotrexate and paclitaxel [26], doxorubicin [27], temozolomide and DNA repair inhibitors [28], metformin/irinotecan [29], and cisplatin [30]. More advanced contributions have reported the development of specifically designed intranasal or intracranial NPs for GBM treatments [31,32]. On the other hand, only a few studies have been reported on NP encapsulation of BBR in cancer [33,34], and in particular, no published contribution has reported the development of PLGA-based NP systems to deliver BBR to glial tumor cells, even if other BBR-NP encapsulation strategies have been proposed for this purpose [24,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…PLGA is from synthetic ones and PLGA-based nanostr�ct�res are �nder wide st�dies beca�se of their extraordinary feat�res s�ch as s�stained dr�g release, biocompatibility, biodegradability, ease of s�rface modification with hydrophilic agents, and ability to load both hydrophilic and hydrophobic substances [13]. There are various studies that have loaded chemothera-pe�tics in PLGA nanoparticles with the aim of GB� treatments [14][15][16].…”
Section: Introductionmentioning
confidence: 99%